2022
DOI: 10.1186/s12913-022-07649-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the knowledge, perception, and practice of healthcare practitioners toward rational use of compounded medications and its contribution to antimicrobial resistance: a cross-sectional study

Abstract: Background Pharmaceutical compounding ensures access of individuals with specific requirements to individualized therapy. However, there is an inconsistency of compounded medication quality. Therefore, advancing the rational use of compounded medication is essential for patient safety and medication effectiveness. Objective The presented study was aimed to investigate the healthcare practitioners’ knowledge, perception, and practice of extemporaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Analogous concerns emerged in a recent study of knowledge, perception, and practice of healthcare practitioners toward compounded medications, notably antimicrobial products, almost half of respondents believed that compounded medications might lack quality and have poor patient compliance. 37 Additionally, a majority expressed concerns regarding potentially inappropriate preparation processes and under-dose administration of compounded medications, with a fear this might contribute to antimicrobial resistance. Whatever the trends in compounding, our study, and others, show that the practice seems destined to stay, in one guise or another.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous concerns emerged in a recent study of knowledge, perception, and practice of healthcare practitioners toward compounded medications, notably antimicrobial products, almost half of respondents believed that compounded medications might lack quality and have poor patient compliance. 37 Additionally, a majority expressed concerns regarding potentially inappropriate preparation processes and under-dose administration of compounded medications, with a fear this might contribute to antimicrobial resistance. Whatever the trends in compounding, our study, and others, show that the practice seems destined to stay, in one guise or another.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Ethiopia with 300 participants including physicians and pharmacists indicated inconsistency of compounded medication quality. Respondents strongly believed that poor quality extemporaneous antimicrobials contribute to anti-microbial resistance development (Assefa et al, 2022). Many pharmacies and institutions develop their own formulary for the frequently compounded products, but this is not sufficient to reduce the possibility of error (Smith et al, 2019).…”
Section: Quality Assurance Of Extemporaneous Preparationsmentioning
confidence: 99%
“…Inappropriately compounded medication results in the administration of insufficient doses and contaminated drugs, which can cause ineffectiveness or toxicity (Assefa et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%